53. Audio/ Videoconferencing Packages: Low cost - Tremblay, Remi; Fyvie, Barb; Koritko, Brenda (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2005)
A comparison was conducted of Voxwire MeetingRoom and iVocalize v4.1.0.3, both Web-conferencing products using voice-over-Internet protocol (VoIP) to provide unlimited, inexpensive, international audio communication, and high-quality Web-conferencing fostering collaborative learning. The study used the evaluation criteria used in earlier reports, including common technical framework, clarity, control, complexity, and costs. Criteria sub-divisions applying to one or more of the products' synchronous and asynchronous components are included in a side-by-side product comparison table. It is concluded that these two highly competitive products provide a serious challenge to the markets of their highly priced rivals. The report also contains a brief summary of GRCLive, another promising conferencing software, which the evaluation team attempted to evaluate, though gave up owing to technical difficulties.